Late Onset Sporadic Dilated Cardiomyopathy Caused by a Cardiac Troponin T Mutation - Morales, Ana (Blackwell Publishing Inc, 2010)
Mutations in TNNT2, encoding cardiac troponin T, commonly shows early onset, aggressive dilated cardiomyopathy (DCM). This observation may influence the decision of whether to undertake clinical genetic testing for TNNT2 in later onset DCM. Further, the trigger for late onset DCM remains enigmatic. A 70‐year‐old woman, previously healthy with a left ventricular ejection fraction of 50%–55% at age 69, presented with DCM of unknown cause and a 4‐month history progressive heart failure requiring cardiac transplantation. Clinical genetic testing revealed a novel TNNT2 R139H mutation but no relevant variants in 18 other DCM genes. Her explanted heart showed partial fatty replacement in the right ventricle. Sequencing for five arrhythmogenic right ventricular dysplasia genes was negative. Functional studies in porcine cardiac skinned fibers reconstituted with the mutant R139H troponin T protein showed decreased Ca(2+) sensitivity at pH 7, characteristic of DCM. Because fatty infiltration may acidify the myocellular environment, maximal force development examined at pH 6.5 was diminished, suggesting a possible environmental trigger. We conclude that the TNNT2 R139H mutation was likely to be disease causing. Further, later age of onset may not be relevant to exclude genetic testing for TNNT2 mutations. Clin Trans Sci 2010; Volume 3: 219–226.